In progress : see inside a renowned lettering artist's creative process - Hische, Jessica (Chronicle Books, 2025)
"This revised edition of design-world darling Jessica Hische's career-spanning art book offers a fascinating inside look at her work in progress, featuring highlights from her most exciting recent projects and new tips for lettering with digital tools. In explanatory captions throughout these pages, Hische guides readers through the phases of each hand-lettered project--for major clients such as Wes Anderson, NPR, Nike, and more--from gathering inspiration and sketching out rough ideas to revising and refining final designs."